2008
DOI: 10.1007/s10338-008-0842-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Specimen Aspect Ratio on Fatigue Life of Closed Cell Al-Si-Ca Alloy Foam

Abstract: Quasi-static and compressive fatigue tests on the closed cell Al-Si-Ca alloy foam specimens with three different aspect ratios were performed. It turned out that the onset of cyclic shortening of foam with a lower aspect ratio took place earlier and the fatigue strength was lower compared with the specimen with a higher aspect ratio, although all the dimensions of specimen satisfied the seven times the cell size criterion, while the quasi-static stress-strain curves were almost same having same Young's modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…They observed an increasing fatigue strength with respect to an increasing relative density of the foams. [113] Kolluri et al subjected closed-cell Al foams to constant amplitude pulsing compressive load in laterally constrained and free condition. [103] Banhart and Brinkers studied powder metallurgy produced Al-Si alloy (Al þ 7 wt% Si) closed cell foams with different relative densities.…”
Section: Fatigue Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed an increasing fatigue strength with respect to an increasing relative density of the foams. [113] Kolluri et al subjected closed-cell Al foams to constant amplitude pulsing compressive load in laterally constrained and free condition. [103] Banhart and Brinkers studied powder metallurgy produced Al-Si alloy (Al þ 7 wt% Si) closed cell foams with different relative densities.…”
Section: Fatigue Propertiesmentioning
confidence: 99%
“…The cyclic compressive tests proved that the foams with higher aspect ratio had higher fatigue limit and the damage accumulation process (i.e., ratchetting) started later. [113] Kolluri et al subjected closed-cell Al foams to constant amplitude pulsing compressive load in laterally constrained and free condition. The results indicated that only the rapid strain accumulation stages behavior were sensitive to the constraint while the early stages of strain accumulation can be considered independent on the radial constraint.…”
Section: Fatigue Propertiesmentioning
confidence: 99%
“…The lifetime of fatigued foams has been measured as a function of the applied stress or strain amplitude with Alporas TM [2,3,9,13], Fraunhofer TM [1], Alulight TM [6,14,15,17], Duocel TM [2,7,8] or Foamtech TM [18] foams and Plansee TM bonded metal hollow-sphere structures [12]. The fatigue strength of all of these foam types increases with the relative density, decreases with increasing stress amplitude, and is highly sensitive to both.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature exceeds the favourite holding temperature, equilibrium hydrogen pressure increases. [16][17][18][19]21 Sufficient foaming kinetics occurs, and hydrogen releasing is accelerated, which causes bubble coalescence very rapidly. The final bubble size and total porosity volume are directly related to hydrogen gas content in the melt due to titanium hydride decomposition and growth rate between bubble and liquid/solid interface.…”
Section: Resultsmentioning
confidence: 99%
“…Among these methods, casting is being widely used for its capability to producing high porosity foams and commercially low cost compared with the others. [15][16][17] Essentially, foamed aluminium products are composite of gaseous pores and metal matrix that contain porosity with a range of 70-90%; thus, controlling the morphology of cell structure and their homogeneous distribution during the foaming process of aluminium melt is important. Most respected properties to these kinds of metal products such as sound and mechanical vibration absorption, heat transfer and mechanical behaviour are related to cell structure.…”
Section: Introductionmentioning
confidence: 99%